Randomized controlled trial of a home-based palliative approach for people with severe multiple sclerosis. (April 2018) - Solari, Alessandra; Giordano, Andrea; Patti, Francesco; Grasso, Maria Grazia; Confalonieri, Paolo; Palmisano, Lucia; Ponzio, Michela; Borreani, Claudia; Rosato, Rosalba; Veronese, Simone; Zaratin, Paola; Battaglia, Mario Alberto; et al.
Background: Evidence on the efficacy of palliative care in persons with severe multiple sclerosis (MS) is scarce. Objective: To assess the efficacy of a home-based palliative approach (HPA) for adults with severe MS and their carers. Methods: Adults with severe MS-carer dyads were assigned (2:1 ratio) to either HPA or usual care (UC). At each center, a multi-professional team delivered the 6-month intervention. A blind examiner assessed dyads at baseline, 3 months, and 6 months. Primary outcome measures were Palliative care Outcome Scale-Symptoms-MS (POS-S-MS) and Schedule for the Evaluation of Individual Quality of Life-Direct Weighting (SEIQoL-DW, not assessed in severely cognitively compromised patients). Results: Of 78 dyads randomized, 76 (50 HPA, 26 UC) were analyzed. Symptom burden (POS-S-MS) significantly reduced in HPA group compared to UC ( p  = 0.047). Effect size was 0.20 at 3 months and 0.32 at 6 months, and statistical significance was borderline in per-protocol analysis ( p  = 0.062). Changes in SEIQoL-DW index did not differ in the two groups, as changes in secondary patient and carer outcomes. Conclusion: HPA slightly reduced symptoms burden. We found no evidence of HPA efficacy on patient quality of life and on secondary outcomes.